Effect of Ground Cover and Shading on Herbaceous Antioxidant Capacity in an Agroforestry System - Visiné Rajczi, Eszter; Benke, Dénes; Hofmann, Tamás (GEORGIKON FOR AGRICULTURE, 2024)
In addition to traditional crops (cereals, vegetables, etc.), agroforestry systems also allow the cultivation of other herbaceous crops such as medicinal plants. Medicinal plants contain a wide range of extractives, many of which have beneficial physiological effects (e.g. antioxidant properties). In the present work the antioxidant content of three species (common sorrel, Rumex acetosa L., ribwort plantain, Plantago lancelota L., dwarf periwinkle, Vinca minor L.) grown in the agroforestry system of the Bajti Nursery under different soil cover methods (mulching, geotextile, bee pasture) and shading (hybrid poplar (Populus euramericana (Dode) Guiner cv. 'I-214') was evaluated. The aim of our studies was to compare which soil covers are the most advantageous on the antioxidant content, and how each plant species responds to different soil covers. Samples were collected three times during the growing season in 2023 (spring, summer, autumn). The antioxidant capacity of the samples was measured by three different methods (TPC, FRAP, DPPH). It was found that the cultivation method resulting in the highest antioxidant capacity varies between plant species.
Keywords: agroforestry; antioxidants; herbs; soil cover; climate change